A Voice Crying out from the Wound—with or without Words: On Trauma, Speech, and Silence1. Issue 4 (4th December 2017) - Welz, Claudia
Abstract: Drawing on memory and trauma studies, psychotherapeutic research, and Holocaust testimonies (in particular those of Wiesel, Semprun, Kulka, and Appelfeld), this article explores the role of speech and silence in the process of working through severe trauma. That which seems "incommunicable" will be considered in regard to the limits of linguistic representation and the problems of communication caused by the interlocutors' avoidance of the past. How can one ensure that recounting traumatic memories does not become an extra risk rather than a remedy?